Food, labor, and beverage cost control a concise guide - Sanders, Edward E. (Waveland Press, 2016)
Foodservice operators have the advantage of using point of sale system applications and tablets. While the POS system is an efficient tool to process information, analyze customer guest check orders, and track employees, it doesn't uproot the need for foodservice operators to understand, process, and interpret that same important information. Edward Sanders, foodservice industry veteran and college professor, introduces culinary and hospitality management students to information essential for the successful management of foodservice operations. His coverage is thorough, and the logically sequenced topics include writing a standardized HACCP Recipe, determining portion costs, using menu popularity percentages, calculating seat turnover rates and server productivity, preparing a sales forecast, completing an income statement, and much more.--Provided by publisher.